PROGRAM PKM KERJASAMA POLITEKNIK LP3I JAKARTA, PRODI LOGISTIK NIAGA DENGAN CENTER OF COMPETENCY (COC): WORKSHOP VIRTUAL LOGISTICS RISK MANAGEMENT, UPAYA PENINGKATAN KAPASITAS MANAJEMEN RISIKO BAGI PRAKTISI DAN AKADEMISI - Karya Bakti Kaban (JURNAL ABDIMAS PLJ, 2026)
The saying goes, "Nothing in this world remains constant except change itself." This is further emphasized by the fact that as soon as we wake up in the morning, we are faced with risk. Simply put, risk is an "unpleasant" event that might occur in the future. No one can be certain of what will happen in the future. Because the future is uncertain, the potential for risk is always present. There is the risk of losing money on investments we choose, the risk of delays in train departures and arrivals, the risk of delayed deliveries, the risk of production interruptions, and many other events that pose risks. Nothing can guarantee certainty. Risk is the impact, the outcome caused by an event. Developing a new product can be risky. There is the risk of the product not meeting standards or specifications. There is the risk of the product not selling. The project being executed may not go as planned. This is where the risk of project failure arises. Uncertainty in the supply chain requires industry players and academics to have a strong understanding of logistics risk management. Logistics plays a crucial role in any organization. Without logistics, there would be no material movement, no operations management, no products, no customer service, no sales, and no profits. Logistics is also expensive. Every logistics activity incurs costs, known as logistics costs, such as procurement costs, transportation costs, storage costs, distribution costs, inventory management costs, and others. Aggregate logistics costs are often measured as a percentage of GDP. The percentage of logistics costs to GDP varies between countries, ranging from 11% to 32%. In Indonesia, aggregate logistics costs account for no less than 24% of GDP. Besides being expensive, logistics activities are also risky because they are closely related to safety, security, health, and environmental issues. This community service activity took the form of an online workshop on Logistics Risk Management, organized by the Commercial Logistics Study Program of the LP3I Jakarta Polytechnic in collaboration with the Center of Competency (CoC). The objective of this activity was to enhance participants' understanding of risk management concepts in the logistics sector, including warehousing, transportation, distribution, and supply chain risks. The workshop was conducted through an online seminar using the g-meet platform, incorporating lectures, discussions, case studies, and a question-and-answer session. Participants included lecturers, students, logistics practitioners, and the general public. The results demonstrated an increased understanding of logistics risk identification and risk mitigation strategies. This workshop is expected to contribute to improving the competency of the public and industry players in implementing effective and sustainable logistics risk management.